(untitled) (Research, Society and Development, 2021)
Background: Bloodstream infections are among the most frequent and serious complications in patients with haematological malignancies. Case presentation: A patient diagnosed with acute myeloid leukemia was admitted to the hospital for chemotherapy induction, developed several episodes of febrile neutropenia. Had bloodstream infection with at least four strains of Gram-negative bacteria, including Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae and Acinetobacter baumanii. The majority showed resistance to ampicillin, cefepime, ceftriaxone, ciprofloxacin and sulfamethoxazole/trimethoprim. blaTEM and blaSIM were detected in P. aeruginosa, blaTEM, blaCTX and blaOXA-48 in E. coli, blaCTX, blaKPC, blaNDM, blaSIM and blaOXA-48 in K. pneumoniae and blaOXA-48 in A. baumannii. Conclusions: The patient was treated with meropenem for 10 days, without progressing from fever episodes, evolved to death.